LEARNING HISTORY OF THE INDEPENDENT CURRICULUM WITH THE DISCOVERY LEARNING MODEL IN CLASS X SMA KEMALA 3 BHAYANGKARI PORONG: PEMBELAJARAN SEJARAH KURIKULUM MERDEKA DENGAN MODEL DISCOVERY LEARNING DI KELAS X SMA KEMALA 3 BHAYANGKARI PORONG - Fatimahtus Zarroh; Aulia Fitriany; M. Khusni Mubarok (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
This study aims to describe the planning, implementation, and evaluation of discovery learning learning model in history subject at SMA Bhayangkari Porong. The research questions asked are :How is the planning of discovery learning learning model in history subject at SMA Bhayangkari Porong,How is the implementation of discovery learning learning model in history subject at SMA Bhayangkari Porong ,How is the evaluation of the discovery learning learning model in history subjects at Bhayangkari Porong High School. This study found that students' learning outcomes were influenced by the learning model applied by educators and students' learning independence. The use of the discovery learning model is considered to be able to increase students' learning independence, which has an impact on improving their learning outcomes. The application of the discovery learning model is also beneficial for educators, because in addition to acting as a facilitator, educators can understand the learning characteristics of students. Based on the research results, it is known that the discovery learning model and learning independence have a positive influence on students' learning outcomes, and are considered more effective in stimulating students to be more active in learning activities